Ureaplasma parvum ventriculitis related to surgery and ventricular peritoneal drainage. Issue 5 (May 2020) - Saje, Andreja; Velnar, Tomaž; Smrke, Barbara; Spazzapan, Peter; Keše, Darja; Kobal, Borut; Beović, Bojana
Abstract: Ureaplasma spp. usually causes genitourinary infections; few reports in the literature describe extragenital infections, usually in immunocompromised patients. We present a case of Ureaplasma parvum ventriculitis in an immunocompetent patient related to ventriculoperitoneal drainage and surgery. Ureaplasma parvum was detected with broad range 16S rRNA PCR and cultured on A8 agar.